Relationship Between Soil Aggregate Stability and Associated Carbon and Nitrogen Changes Under Different Ecological Construction Measures in the Karst Region of Southwest China - Li, Meiting; Wang, Keqin; Ma, Xiaoyi; Fan, Mingsi; Li, Biyu; Song, Yali (Agriculture (Basel), 2025)
As the fundamental unit of soil structure, soil aggregates play a crucial role in enhancing soil carbon and nitrogen storage, thereby supporting soil fertility and overall health, particularly in fragile karst regions. This study aims to quantify the effects of various ecological construction measures on soil aggregate stability, including focusing on geometric mean diameter (GMD), mean weight diameter (MWD), and K values, as well as aggregate-related organic carbon (SOC) and total nitrogen (TN), soil mechanical composition, and aggregate content. The ecological construction measures examined include plantation forests (Y7th–rgl), restored forests (Y6th–zr), fruit forests (Y6th–jgl), and contour reverse slope terraces (Y1th–crt). Compared to sloping farmland, contour reverse slope terraces, with their distinctive priority induction function, significantly increased the content of medium-fine particle aggregates, greater than 87%. Among the ecological construction measures, plantation forests exhibited the highest aggregate stability, with an average increase ranging from 8% to 157%. Notably, microaggregates, regardless of size, possessed the highest carbon and nitrogen contents, contributing significantly to soil carbon and nitrogen pools. Furthermore, both plantation and contour reverse slope terrace treatments demonstrated an equal contribution of carbon and nitrogen across all aggregate sizes. The partial least squares path modeling (PLS-PM) analysis indicates that land use type and the content of carbon and nitrogen pools are the primary factors influencing soil aggregate stability. These findings suggest that plantations are particularly effective in enhancing soil and water conservation in fragile karst areas, while the contour reverse slope terrace method shows potential for stabilizing soil structure over extended time scales due to its unique “preferential entrainment” function.